Laron syndrome - from man to mouse lessons from clinical and experimental experience - Laron, Zvi; Kopchick, J. (Springer Berlin, 2010)
Laron syndrome (LS), or primary growth hormone (GH) insensitivity, was first described in 1966. Since then, many patients worldwide have been diagnosed with LS, which involves defects in the GH receptor that cause combined congenital deficiency of GH and IGF-I activities. In this comprehensive book the authors draw upon 50 years of multidisciplinary clinical and investigative follow-up of the large Israeli cohort of LS patients. The genetic basis of the syndrome is fully considered, and all aspects of the pathophysiology of IGF-I deficiency are described. Data derived from the recently generat.